3D Analytical model of drag and lift force for a conductive plate moving above a Halbach magnet array. (August 2018) - Tongyu, Shi; Dazhi, Wang
When a conductive plate moves above a Halbach magnetic source, a magnetic field will be created in the air gap. This field induces eddy currents in the plate and creates drag and lift forces simultaneously. This phenomenon may be applied into eddy current brakes, couplings or magnetic levitation systems. In this paper, by utilizing the derived analytical field solutions of the Maxwell equations with magnetic scalar potential and magnetic field strength, the 3D lift and drag forces, and the flux density distribution in the air gap are predicted and analysed in the steady-state condition. Calculation results produced by analytical model are compared with those from the 3D finite element method. A prototype of the disk-type permanent magnetic eddy-current coupling has been manufactured to validate the accuracy of the 3D analytical model. The results confirm that, compared with 2D analytical model from the papers that had already published, the results calculated by the 3D analytical model have a higher accuracy in performance analysis. Finally, the characteristics of different kinds of magnet arrays are compared based on the proposed model, and several main problems are analysed and discussed.